Fractionalized excitations in the partially magnetized spin liquid candidate YbMgGaO4. Issue 1 (December 2018) - Shen, Yao; Li, Yao-Dong; Walker, H.; Steffens, P.; Boehm, M.; Zhang, Xiaowen; Shen, Shoudong; Wo, Hongliang; Chen, Gang; Zhao, Jun
Abstract Quantum spin liquids (QSLs) are exotic states of matter characterized by emergent gauge structures and fractionalized elementary excitations. The recently discovered triangular lattice antiferromagnet YbMgGaO4 is a promising QSL candidate, and the nature of its ground state is still under debate. Here we use neutron scattering to study the spin excitations in YbMgGaO4 under various magnetic fields. Our data reveal a dispersive spin excitation continuum with clear upper and lower excitation edges under a weak magnetic field (H  = 2.5 T). Moreover, a spectral crossing emerges at the Γ point at the Zeeman-split energy. The corresponding redistribution of the spectral weight and its field-dependent evolution are consistent with the theoretical prediction based on the inter-band and intra-band spinon particle-hole excitations associated with the Zeeman-split spinon bands, implying the presence of fractionalized excitations and spinon Fermi surfaces in the partially magnetized QSL state in YbMgGaO4 . Recent experiments have indicated that YbMgGaO4 may be a quantum spin liquid with spinon Fermi surfaces but additional evidence is needed to support this interpretation. Shen et al. show weak magnetic fields cause changes in the excitation continuum that are consistent with spin liquid predictions.